A study of grain boundary precipitation of nano-scale Cu-rich phase in polycrystalline Fe–Cu binary alloys using a phase-field method - Mingguang Wei; Tongguang Zhai; Kang Wang (Journal of Materials Research and Technology)
In this study, a phase-field model was developed to simulate quantitatively, for the first time, the precipitation process of the Cu-rich phase at grain boundaries in polycrystalline Fe–Cu alloys with different Cu contents at different aging temperatures. The results showed that, with increasing segregation of Cu atoms at grain boundaries, the incubation time of the Cu-rich phase was decreased, and the number density of the Cu precipitates increases at the boundaries but decreases within grains. With lower initial Cu content or at a higher temperature, a relatively small number of Cu precipitates could preferentially be formed at grain boundaries through a nucleation-growth mechanism. With increasing the initial Cu content or decreasing temperature, precipitation of the Cu-rich phase occurred by a pseudo-spinodal decomposition, resulting in formation of the Cu precipitates in a large number at grain boundaries and inside grains over a shorter period. This work paved the way to applying the phase-field modeling technique to further quantify the precipitation behaviors of Cu-rich phase in polycrystalline Fe–Cu alloys.